Pedigree of Dualistic and Non-Dualistic Media: Grasping Extramedial Meanings Journal for Religion, Film and Media - Stefan Lorenz Sorgner (Journal for Religion, Film and Media, 2016)
The article provides suggestions concerning the cultural relevance and embeddedness of dualist and non-dualist media and demonstrates that the presence or absence of certain types of media has extra-medial relevance that can contain ethical, political, and social meanings. When I am talking about these kinds of dualities I am referring to distinctions like the one between good and evil, mind and body, culture and nature, the material and the immaterial or the organic and the inorganic. The contemporary examples I mention paradigmatically represent the phenomenon in question. However, several other artists, composers and designers are central figures, too, e.g. Patricia Piccinini, Eduardo Kac, Stelarc.